Pentingnya Pemisahan Kekuasaan Dalam Mempertahankan Pemerintahan Yang Seimbang - Azhari Sellomitha Fodhi; Eky Lestari; Tyara Fridayanti Nuramalina; Ghaida Raisya As-Syifa (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The division of power into three branches put forward by two experts called trias politica which is generally divided into legislative, executive, and judicial powers, the fourth branch put forward by Hans Kelsen in the statement of ensuring regime stability requires a fourth branch referred to as the Constitutional Court which is believed to be the guardian of the stability of the other three branches by maintaining the constitution in the party government and with this function can determine many other characteristics. By using a normative method that aims to understand and interpret the rules of law contained in the constitution of state administration in Indonesia, ensuring the suitability of each rule of law with the norms that apply in the context of writing articles on constitutional law. The data used in this paper is secondary data. This existence of a balanced government in the state administration ensures that there is a fair contribution of power in each power-sharing system with the aim of monitoring and balancing each other to prevent abuse of power and ensure the fulfillment of citizens’ rights.